Dattātreya : the immortal guru, yogin, and avatāra : a study of the tranformative and inclusive character of a multi-faceted Hindo deity - Rigopoulos, Antonio, 1962- (Albany : State University of New York Press, 1998)
The book presents the multi-faceted Hindu deity Dattatreya from his Puranic emergence up to modern times. Devotion to Dattatreya cuts through all social and religious strata of Indian society: among his adepts we find yogis, Brahmans, faqirs, Devi worshippers, untouchables, thieves, and prostitutes. This book explores all primary religious dimensions: myth, doctrine, ritual, philosophy, mysticism, and iconography. The comprehensive result offers a rich fresco of Hindu religion as well as an understanding of Marathi integrative sprituality: precisely this complexity of themes constitutes Dattatreya's uniqueness. -- Provided by publisher.
Includes bibliographical references (pages 265-295) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Dattātreya -- (Hindu deity); Dattātreya (Divinité hindoue); RELIGION -- Hinduism -- Theology; Dattātreya (Hindu deity)